012 164 second conceptual film without dialogue, successfully conveys the impor- tance of early intervention in MS. Issue 6 (27th May 2022) - Wilkie, David; Middleton, Rod; Cook, James; Nicholas, Richard
Abstract : Objectives: Early treatment in MS often needs to be started in the absence of symptoms. This preventa- tive approach is a complex concept to convey to a naïve population. We produced a 164 second film without dialogue with the aim of assessing whether it delivered its message successfully. Methods: PwMS were recruited from clinics, the UK MS Register and a general population. Based upon industry standards, pre-specified outcomes included 50% viewer retention equivalent to watching 30 seconds and 50% understanding of 4 concepts. The film was incorporated into a website explaining the concepts and participants answered questions about the concepts. Results: Viewer retention was 887/1102 (80%) in the total population with an average viewing duration of 149/164 seconds (91%), significantly above the pre-specified outcome percent (p<0.0001). In the MS Register population 757/959 (78.9%) pwMS had total understanding (4/4 concepts) compared with 29/42 (69%) in pwMS from outpatients and 136/149 (91%) in the general population. Understanding in all cohorts were significantly above the pre-specified outcomes (p<0.0001) with greatest understanding in the general population versus pwMS (p<0.0001). Conclusions: A short, targeted film successfully conveys the importance of early intervention to both MS and non-MS audiences. d.wilkie@imperial.ac.uk